ANALISIS PENGARUH INFILTRASI PADA AC SPLIT INVERTER TERHADAP KECEPATAN PENDINGINAN DAN PENGHEMATAN ENERGI - Iskendar; Eko Dwi Wahono (Teknobiz : Jurnal Ilmiah Program Studi Magister Teknik Mesin, 2020)
In this study an analysis of the relationship between infiltration with cooling speed and analysis of the relationship between infiltration with energy savings in AC Inverters and Non-Inverter ACs. Data collected include time, door opening fully open, ¾, ½, and ¼, indoor temperature (TD), outdoor temperature (TL), current, voltage and power factor on AC Inverters and Non-Inverter ACs. From the temperatur data in space and time and door opening, infiltration and cooling speed are calculated. Data from current, voltage and power factor are then calculated energi. After infiltration, cooling speed and energy obtained from calculations, a simple linear regression analysis and Independent Sample T-Test analysis are performed. Regression analysis was performed to determine the relationship between infiltration and cooling speed. The relationship between infiltration and energi savings, this analysis is carried out in a room that uses AC Inverter and AC Non Inverter. After that the analysis of the Independent Sample T-Test between the energi consumption of AC Inverters and AC Non Inverters. In addition to analysis with software, calculations are also carried out so that energi consumption can be known to save AC Inverter after that, then conclusions can be drawn.